Exploring Determinants and Future Trends of Halal Marketing: Systematic Literature Review - Edwin Zusrony; Muhammad Sholahuddin; Imronudin Imronudin; Luki Sri Anggorowati; Endang Kustami; Andreas Sang Aji Purbokusumo (Journal of Management and Creative Business, 2026)
Research on halal label-based marketing shows a significant increase in publications from 2020 to 2024, reflecting the growing global interest in halal-certified products and services. This study used a systematic literature review (SLR) method with the PRISMA technique. The research focuses vary, ranging from halal awareness, religiosity, and consumer trust, to cultural accessibility, sustainability, luxury consumption, and innovative branding. Key trends highlight the importance of halal certification in building consumer trust and loyalty, as well as the influence of religiosity on behavioral intentions. Topics such as sustainable halal practices and halal branding in non-Muslim markets indicate a shift towards aligning with global trends and expanding market opportunities. Overall, the literature highlights the crucial role of halal-based marketing in meeting the needs of Muslim consumers and attracting a wider audience, as well as the potential to drive business performance and innovation, while remaining compliant with Islamic principles.